Parallel inductor multilevel current source inverter with energy-recovery scheme for inductor current balancing / Nik Fasdi Nik Ismail - Nik Fasdi , Nik Ismail (2019)
In this study, the analysis and design of a single phase five-level parallel inductor multilevel current source inverter (MCSI) with energy recovery circuit is presented. The proposed inverter operates in a continues-conduction-mode (CCM) and the objective is to obtain sinusoidal output current with a low current total harmonic distortion (THD). In recent active developments, the current fed-converters have increasingly become popular because of their inherent advantages over voltage fed-converters. However, the existing current multilevel inverter topologies have many weak points and unpractical to be realized for some applications due to large DC link input inductor size, the complexity in balancing the sharing inductor currents, high switching frequency operation for power switches, low output efficiency and complex circuit structures with excessive count of components. Almost all the reported topologies apply redundancy switching technique with the different switching state combinations to achieve balancing of the sharing inductor current or intermediate current level. However, to ensure the effectiveness of the redundancy switching technique, the input DC current needs to be constant with a small current ripple. Therefore, a large size of DC link inductor is needed to achieve the constant input DC current. In contrast with the existing topologies, the proposed energy recovery circuit in this study provides a simple switching technique to balance the intermediate inductor currents with single switching state for each output current level in the operation of multilevel inverter current source (MCSI) topology. In addition, a chopper circuit with a smaller inductor size is employed and integrated with the inverter in order to replace the large and bulky DC link inductor. As a result, a simple converter structure for a five-level multilevel current source inverter (MCSI) can be achieved. This work has been focused to overcome the weak points of existing multilevel current source topologies by proposing a parallel inductor with energy recovery scheme for a five-level MCSI topology. The comprehensive analysis study between the existing topologies and the proposed topology has been made. The results shows that the proposed MCSI with energy recovery scheme has improved some of the drawbacks of the existing MCSIs such as circuit structure and inductor current balancing technique and also improved the performance and efficiency of the inverter. The performance and the characteristic of the proposed topology is analyzed through computer simulation and verified by experiment.